Customs relationship to drugs: the notion, structure and signs - Шевчук, О. М. (Theory and practice of jurisprudence, 2016)
Article is devoted to customs legal relations with respect to movement of drugs across the customs border of Ukraine. We present the concept of customs legal relations on drugs, define subject, object and content of these customs relation